Purchasing behavior and factors determinants of repurchase intention among millennial consumers of the e-commerce platforms - Quique Cobos, Dalia Esther (2024)
Objective: To analyze the purchasing behavior of millennials on the e-commerce platforms, identifying the key factors that influence their repurchase intention. Materials and methods: A non-experimental quantitative approach of cross-sectional design was used, in which data were collected using a structured questionnaire applied to 400 participants. Data analysis included both descriptive and inferential statistics, using Pearson correlation analysis to assess the relationship between trust, satisfaction, and repurchase intention. Results: The results reveal that trust (0.78) and satisfaction (0.83) have a significant positive correlation with repurchase intention. Furthermore, 50% of participants use e-commerce platforms on a weekly basis, highlighting the relevance of user experience in customer retention. Conclusions: Trust and satisfaction are the most important factors determinants influencing millennial consumers’ loyalty toward e-commerce platforms. Companies must continue to invest in improving the user experience to encourage repeat purchase intentions and thus ensure fidelization.